Silviculture conditions and wood properties of Samanea saman and Enterolobium cyclocarpum in 19-year-old mixed plantations - Obando, M.F.; Moya, R. (Forest Systems, 2013)
Aim of study: The objective of this work is to examine wood properties of a mixed plantation of Samanea saman and Enterolobium cyclocarpum, combined with native species of Costa Rica.Area of study: Mixed plantation in dry tropical zone of Costa Rica.Material and Methods: It was measured by total diameter, heartwood, bark thickness, several physical wood properties (green density, specific gravity, volumetric, tangential and radial shrinkage and moisture content) and wood color.Main results: The largest of this diameter are reached when S. saman is planted with E. cyclocarpum, E. cyclocarpum and Swietenia macrophylla and Simarouba glauca. Meanwhile the largest total diameter and heartwood in E. cyclocarpum was found when this species is planted with Dalbergia retusa. Heartwood percentage, bark percentage, and some physical properties are not affected when S. saman or E. cyclocarpum are planted with other species. However, parameters of wood color were affected mixture plantation of S. saman or E. cyclocarpum with other species. The lowest difference between wood from mixed plantations and wood from trees growing in native forests is produced when S. saman is mixed with E. cyclocarpum, but this last species is mixed with Hymenaea courbaril and produced wood with the lowest difference in wood color compared to trees growing in the natural forest.Research highlights: S. saman and E. cyclocarpum tress planted in a mixed plantation produce variation in breast diameter, physical properties, heartwood percentage and wood color.Keywords: silvicultural condition; wood properties; tropical species; plantation species.